Akulturasi Islam dan Nilai Pendidikan Islam dalam Tradisi Tampung Tawar di Komunitas Dayak Muslim - Cipta Rahman, Nabilah; Normuslim; Muslimah (Kartika: Jurnal Studi Keislaman, 2026)
This article discusses the acculturation of Islam in the Tampung Tawar tradition and the educational values embedded within it among the Dayak Ngaju Muslim community in Parenggean Village, Kotawaringin Timur Regency, Central Kalimantan. The Tampung Tawar ritual serves as a traditional ceremony that symbolizes purification, protection, the invocation of safety, and the expression of gratitude. As Islam gradually spread among the Dayak people, this ritual experienced a transformation in its values and meanings. Using a qualitative descriptive approach, data were collected through direct observation, interviews, and document analysis. The findings show that Islamic elements such as the recitation of Qur’anic verses, Arabic prayers, and the emphasis on purity and charity have been integrated into the performance of Tampung Tawar. The Islamic educational values contained in the ritual include religiosity, deliberation, cleanliness, and gratitude. This tradition functions as a medium for transmitting Islamic values and teachings to younger generations while at the same time preserving local cultural heritage. The study concludes that Islamic education can coexist harmoniously with local wisdom without losing the essence of its teachings.